2018
DOI: 10.1093/jas/sky291
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a single dose of subcutaneous meloxicam prior to band or knife castration in 1-wk-old beef calves: II. Inflammatory response and healing1

Abstract: The aim of this study was to evaluate the effect of a single dose of subcutaneous (s.c.) meloxicam administered at the time of knife and band castration on inflammatory response and wound healing over 56-d post-castration. Seventy-two Angus crossbred calves (47.3 ± 6.70 kg of body weight [BW] and 7 to 8 d of age) were randomly assigned according to a 3 × 2 factorial design assessing castration method: sham (CT), band (BA), and knife (KN) castration, and pain mitigation: non-medicated (NM) and medicated calves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 37 publications
1
17
1
Order By: Relevance
“…However, ear tagging of both sexes and castration of males resulted in increased expression of specific behaviours previously found to be elevated after rubber ring castration and ear tagging but not in response to sham treatment (e.g., [15,18,21]) suggesting that the calves did show behavioural responses that were specifically indicative of pain. Several of these behaviours have been shown to be mitigated by pain relief [22,23]. Furthermore, it was not possible to prevent the cow from viewing the handling of her calf.…”
Section: Discussionmentioning
confidence: 99%
“…However, ear tagging of both sexes and castration of males resulted in increased expression of specific behaviours previously found to be elevated after rubber ring castration and ear tagging but not in response to sham treatment (e.g., [15,18,21]) suggesting that the calves did show behavioural responses that were specifically indicative of pain. Several of these behaviours have been shown to be mitigated by pain relief [22,23]. Furthermore, it was not possible to prevent the cow from viewing the handling of her calf.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of published reports on hair cortisol have dealt with adult cattle, and there are few studies in calves. 14,20,21 Fifteen-day-old healthy calves had higher hair cortisol concentrations than 2-year-old cows, 14 analogous to the observation in humans that children have higher hair cortisol concentrations than adults. 3 A study on the effect of rest stops during long-distance transport of beef calves found that calves that were transported in a trailer for 15 hours, then unloaded, rested, fed and watered for 15 hours before being transported for another five hours had lower hair cortisol concentrations 25 days later than calves that remained in the trailers during the rest period without food and water.…”
Section: Slaughter and Procurement Of Hair And Organ Samples Introducmentioning
confidence: 83%
“…20 Band-castrated, one-week-old calves that did not receive pain medication had higher hair cortisol concentrations 56 days later compared with calves that underwent the same procedure and received one dose of subcutaneous meloxicam. 21 In contrast, veal calves raised under a husbandry system that fulfilled minimal welfare requirements had the same hair cortisol concentration as calves raised under more stringent welfare conditions. 31 To our knowledge, the effect of bronchopneumonia on hair cortisol concentration of calves has not been investigated even though bronchopneumonia is one of the most common diseases of veal calves.…”
Section: Slaughter and Procurement Of Hair And Organ Samples Introducmentioning
confidence: 98%
“…In studies of pre-weaned calves, Brown et al (2015) observed improved gain for the first month after castration with M administration to calves surgically castrated near birth, but there was no effect of M administration on weaning weight. However, Meléndez et al (2018a) found M administration reduced circulating concentrations of substance P, white blood cell counts, and number of tail flicks after surgical castration of 1-week-old calves, and Marti et al (2018) observed reduced hair cortisol concentration by M administration to 1-week-old, band castrated calves. Buccal M administration prior to surgical castration reduced pain behavior and inflammation following surgical castration of 2- to 4-month-old calves ( van der Saag et al, 2018 ).…”
Section: Introductionmentioning
confidence: 98%
“…Meloxicam can be administered orally with a long half-life in ruminants and pre-ruminants ( Coetzee et al, 2009 ; Mosher et al, 2012 ). There have been multiple studies of the use of M at the time of castration in weaned calves ( Coetzee et al, 2012 ; Repenning et al, 2013 ; Roberts et al, 2015 ; Olson et al, 2016 ; Marti et al, 2018 ; Meléndez et al, 2018b ).…”
Section: Introductionmentioning
confidence: 99%